Nuevo horizonte de sentido histórico, crisis de la modernidad y movimientos de la sociedad. El legado teórico de Aníbal Quijano - Mejía Navarrete, Julio Victor (2019)
In a period, that gestates retrograde and nostalgic thoughts, in the culture of despair. It is fundamental to analyze the theoretical proposal of Aníbal Quijano on the emergence of a horizon of historical sense. In which the development of another imaginary of the future based on moral values of human justice, comes as result of the transformation responses generated in the same forces and movements of society.